Hollow NiCo2Se4 microspheres composed of nanoparticles as multifunctional electrocatalysts for unassisted artificial photosynthesis. (1st September 2018) - Wang, Min; Ge, Hongtao; Jin, Zhitong; Wang, Yuhang; Zhang, Meirong; Zheng, Gengfeng; Wang, Zhong-Sheng
Abstract: Hollow NiCo2 Se4 microspheres composed of nanoparticles are prepared using NiCo-glycerate microsphere as the sacrificial template. The NiCo2 Se4 electrode has multiple functions, which can electrocatalyze both the reduction of triiodide in quasi-solid-state dye-sensitized solar cells (QSSDSSCs) and the overall water splitting. The hollow NiCo2 Se4 microspheres as the electrocatalyst achieves power conversion efficiency of 8.26% for QSSDSSCs and 10 mA cm −2 of current density at 1.85 V for the two-electrode water-splitting reaction of 0.1 mol dm −3 KOH aqueous solution. Three single QSSDSSCs connected in series, under 1-sun illumination, can drive the overall water-splitting device efficiently with solar-to-hydrogen efficiency of 5.18% and good stability, where the unassisted artificial photosynthesis employs only one kind of electrocatalyst. Graphical abstract: Hollow NiCo2 Se4 microspheres assembled with nanoparticles are synthesized using a sacrificial template and applied as the electrocatalyst of an unassisted artificial photosynthesis device. Three single QSSDSSCs connected in series under 1-sun irradiation can drive an overall water-splitting cell with solar-to-hydrogen efficiency of 5.18%. Image 1 Highlights: The NiCo2 Se4 hollow microspheres composed of nanoparticles are prepared. The NiCo2 Se4 has good electrocatalytic activity on the reduction of triiodide. The NiCo2 Se4 is efficient for the hydrogen/oxygen evolution reactions. The quasi-solid-state solar cells can drive overall water splitting cell. The artificial photosynthesis device yields solar-to-hydrogen efficiency of 5.18%.